Enseñar matemática en el nivel inicial y el primer ciclo de la EGB - PANIZZA, Mabel comp. (PAIDOS, 2005)
Otros descriptores: PREESCOLAR; NUMEROS NATURALES. Otros autores: BARTOLOME, Olga; BROITMAN, Claudia; FREGONA, Dilma; ITZCOVICH, Horacio; QUARANTA, María Emilia; RESSIA DE MORENO, Beatriz; SAIZ, Irma Elena; TARASOW, Paola; WOLMAN, Susana